2003
DOI: 10.1088/0953-8984/15/28/316
|View full text |Cite
|
Sign up to set email alerts
|

The de Haas–van Alphen effect in URu2Si2under pressure

Abstract: We carried out a de Haas-van Alphen (dHvA) experiment under pressure on a heavy-fermion superconductor, URu 2 Si 2 .The dHvA frequency, which corresponds to a nearly spherical Fermi surface, increases slightly with increasing pressure, while the corresponding cyclotron mass decreases considerably. Neither the dHvA frequency nor the cyclotron mass exhibit any abrupt change at the critical pressure of 1.5 GPa. The present result is thus inconsistent with a recent phase-separation proposal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
43
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 5 publications
14
43
1
Order By: Relevance
“…Compared with the drastic change of the α 1 , the coefficient α 2 shows only weak pressure dependence, which is consistent with the fact that the Fermi surface topology does not change across the critical pressure P x studies. 17,18 This suggests the validity of the analysis with the expression for the electrical transport in URu 2 Si 2 . We speculate that the scattering process of the quasiparticles on most regions of the Fermi surface obeys the Fermi liquid theory but the process in specific regions of the surfaces deviates from the theory in the HO phase.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Compared with the drastic change of the α 1 , the coefficient α 2 shows only weak pressure dependence, which is consistent with the fact that the Fermi surface topology does not change across the critical pressure P x studies. 17,18 This suggests the validity of the analysis with the expression for the electrical transport in URu 2 Si 2 . We speculate that the scattering process of the quasiparticles on most regions of the Fermi surface obeys the Fermi liquid theory but the process in specific regions of the surfaces deviates from the theory in the HO phase.…”
mentioning
confidence: 73%
“…On the contrary, recent Fermi surface studies under high pressure across P x suggest the similarity of the Fermi surface topology between the HO and LAFM phases. 17,18 To gain further insights into the electrical transport in URu 2 Si 2 , we now analyze the data in the temperature regions from T l to 3.0 K using the expression ρ = ρ 0 + α 1 T + α 2 T 2 that has been used in the analysis of the anomalous electrical transport in the organic superconductors, the iron pnictide superconductors, and the high-T c cuprate superconductors. [19][20][21] The expression assumes two independent scattering rates: one is an isotropic rate in k space that gives the T 2 term in the resistivity and the other is anisotropic one that does the T -linear term.…”
mentioning
confidence: 99%
“…The latter phase diagram was recently corroborated by measurements of electrical resistivity and ac calorimetry [28]. However, several details regarding the HO-AFM phase boundary are unresolved: the de Haas-van Alphen effect appears insensitive to the HO-AFM transition [29], as does the high-magnetic-field phase diagram [30], while the SC phase has also been observed to persist at pressures significantly greater than 5 kbar in magnetization [31] and electrical resistivity measurements [32,33].…”
Section: Introductionmentioning
confidence: 83%
“…Evidence for the heterogeneous coexistence of the HO and AFM states below 15 kbar was suggested from 29 Si NMR measurements [16,17] and µSR measurements indicated that the AFM volume fraction emerged at ≈ 5 kbar (extrapolated to T = 0 K) [18,19]. This general pressure-dependence was corroborated by measurements of dilation under pressure [20], while measurements of ac magnetic susceptibility demonstrated the suppression of the SC state at approximately 4 kbar, at the T = 0 K onset of the HO-AFM transition [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation